Evolving concepts on regulation and function of renin in distal nephron - Prieto, Minolfa C. (2012)
Sustained stimulation of the intrarenal/intratubular renin–angiotensin system in a setting of elevated arterial pressure elicits renal vasoconstriction, increased sodium reabsorption, proliferation, fibrosis, and eventual renal injury. Activation of luminal AT(1) receptors in proximal and distal nephron segments by local Ang II formation stimulates various transport systems. Augmented angiotensinogen (AGT) production by proximal tubule cells increases AGT secretion contributing to increased proximal Ang II levels and leading to spillover of AGT into the distal nephron segments, as reflected by increased urinary AGT excretion. The increased distal delivery of AGT provides substrate for renin, which is expressed in principal cells of the collecting tubule and collecting ducts, and is also stimulated by AT(1) receptor activation. Renin and prorenin are secreted into the tubular lumen and act on the AGT delivered from the proximal tubule to form more Ang I. The catalytic actions of renin and or prorenin may be enhanced by binding to prorenin receptors on the intercalated cells or soluble prorenin receptor secreted into the tubular fluid. There is also increased luminal angiotensin converting enzyme in collecting ducts facilitating Ang II formation leading to stimulation of sodium reabsorption via sodium channel and sodium/chloride co-transporter. Thus, increased collecting duct renin contributes to Ang II-dependent hypertension by augmenting distal nephron intra-tubular Ang II formation leading to sustained stimulation of sodium reabsorption and progression of hypertension.